BIOMECHANIC STUDY OF GRAFT BONE TUNNEL MODEL IN ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION USING INTRATUNNEL ALLOGENIC BONE MARROW MESENCHYMAL STEM CELLS (BM-MSCs) AND VASCULAR ENDOTHELIAL GROWTH FACTOR (VEGF) - faridyan, brian vicky (Journal of Stem Cell Research and Tissue Engineering, 2018)
Successful anterior cruciate ligament (ACL) reconstruction using tendon graft requires good and rapid integration between the tendon graft and the bone tunnel. The strength of the tendon-bone tunnel graft in the initial phase is very important to facilitate aggressive rehabilitation and as early as possible to support rapid recovery to normal activities. The objective of this study was to determine ultimate tension strength (UTS) on the femoral tendon-bone tunnel graft model after reconstruction of anterior cruciate ligament (ACL) by administering allogenic bone marrow mesenchymal stemcells (BM-MSCs) and vascular endothelial growth factor (VEGF) intratunnel in experimental animals. The design of this research was Post-Test Only Control Group Design using 24 rabbits divided into treatment and control group. Biomechanical evaluation was done at week 3 and 6. Evaluation at week 3 found ultimate tension strength of treatment group significantly higher than control (p <0,05). In the 6th week evaluation, Ultimate tension strength was found that the treatment group significantly higher than the control group (p <0.05). Ultimate tension strength at week 3 did not differ significantly with week 6 (p> 0.05). Intravenous administration of BM-MSCs and VEGF on ACL reconstruction increased ultimate tension strength in graft-bone tunnel significantly since week 3. The study of Ferdiansis et al using BM-MSCs and VEGF intraarticular, only showed a significant increase in ultimate tension strength in graft-bone tunnel since week 6. Comparison of this method indicates acceleration in incorporation of tendon graft with bone tunnel on intratunnel method better thaninvitro intraarticular method.Keywords : Anterior cruciate ligament, allogenic bone marrow mesenchymal stem cells, vascular endothelial growth factor and biomechanic study.